Desenvolvimento sustentável: Ituiutaba(MG) à luz dos ODS da Agenda 2030 da ONU - Silva, Sandra Aparecida da (2024)
Sustainable Development is a fundamental concept, yet its applicability is still in early stages. The UN's 2030 Agenda sets forth 17 Sustainable Development Goals (SDGs) grouped into five main areas (People, Prosperity, Peace, Partnerships, and Planet). The municipalization of SDG indicators can be an effective strategy as local realities are not always reflected in national indices. The research aimed to analyze Ituiutaba's situation regarding the 2030 Agenda, considering topics such as Public Health (SDG 3), Basic Sanitation (SDG 6), Electricity (SDG 7), and Sustainable Cities (SDG 11). The methodology employed considered the observation of local and national data to measure indicators and identify shortcomings in the implementation of the 2030 Agenda's action plans. The performance of the Unified Health System (SUS) and Primary Health Care policies were discussed concerning SDG 3, with reports on the Dengue panorama in Brazil and actions in Ituiutaba. In SDG 6, Ituiutaba achieved goals related to water supply and sewage collection. SDG 7 showed success in the goal of access to electricity. In SDG 11, practices such as the "Busão do Povo" public transportation and solid waste management were observed. Ituiutaba's results differ from national averages, highlighting the importance of local data for the success of the 2030 Agenda. The IDCS-BR is a fundamental tool for analyzing local indicators. The final considerations on SDGs 3, 6, 7, and 11 emphasize the urgent need for awareness and engagement of municipalities and citizens in implementing the 2030 Agenda. Public sector commitment is essential for success, involving the entire community as an active component. The interconnectedness between health, water, energy, and urban planning is evident, show that the success of one SDG depends on the other and complements the entire sustainable development process.